Ambulatory blood pressure monitoring tolerability and blood pressure status in adolescents: the SHIP AHOY study. Issue 1 (February 2019) - Hamdani, Gilad; Flynn, Joseph T.; Daniels, Stephen; Falkner, Bonita; Hanevold, Coral; Ingelfinger, Julie; Lande, Marc B.; Martin, Lisa J.; Meyers, Kevin E.; Mitsnefes, Mark; Rosner, Bernard; Samuels, Joshua; et al.
Abstract : Background: Ambulatory blood pressure monitoring (ABPM) provides a more precise assessment of blood pressure (BP) status than clinic BP and is currently recommended in the evaluation of elevated BP in children and adolescents. Yet, ABPM can be uncomfortable for patients and cumbersome to perform. Objective: Evaluation of the tolerability to ABPM in 232 adolescent participants (median age: 15.7 years, 64% white, 16% Hispanic, 53% male) in the Study of Hypertension In Pediatrics Adult Hypertension Onset in Youth and its potential effects on ABPM results. Participants and methods: Ambulatory BP status (normal vs. hypertension) was determined by sex and height-specific pediatric cut-points. Participants were asked to rank their wake and sleep tolerability to ABPM from 1 (most tolerant) to 10 (least tolerant); those with tolerability score of at least 8 were considered ABPM intolerant. Results: Forty-three (19%) participants had wake ambulatory hypertension (HTN), 42 (18%) had sleep ambulatory HTN, and 64 (28%) had overall (wake and/or sleep) ambulatory HTN. Forty (17%) participants were intolerant to ABPM during wake hours and 58 (25%) were intolerant during sleep. ABPM intolerance during wake (but not sleep) hours was independently associated with wake (odds ratio: 2.34, 95% confidence interval: 1.01−5.39) and overall (odds ratio: 2.94, 95% confidence interval: 1.21−7.18) ambulatory HTN. Conclusion: Poor tolerability to ABPM is associated with a higher prevalence of ambulatory HTN in adolescents, and should be taken into consideration at time of ABPM interpretation.